Polyurethane resin with super-hydrophobic surface and preparation method thereof

By introducing fluorinated modified nanoparticles and POSS structures into polyurethane resin, the problems of hydrophobicity and nanofiller dispersion of polyurethane materials are solved, which significantly improves the hydrophobicity, mechanical properties and chemical stability of the material, and forms superhydrophobicity of the surface and Good mechanical properties.

CN119285899AInactive Publication Date: 2025-01-10NINGBO HARVEST POLYMER TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411636994.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The hydrophobicity of polyurethane materials is poor, especially in humid environments, which leads to a decline in performance. The dispersion of nanofillers in the polyurethane matrix is ​​serious, affecting the mechanical properties of the material.

Method used

Fluorinated modified nanoparticles were prepared by reacting 2,2'-diallyl bisphenol A with fluorothiol monomers, and modified with tetramethoxysilane and nanozinc oxide, followed by paraformaldehyde React with aminopropyl isobutyl POSS to form fluorinated modified nanoparticles grafted POSS, and finally with diisocyanate monomer, 3,3-bis(hydroxymethyl)azetidone and diol in nitrogen The reaction was carried out under protection to produce a superhydrophobic polyurethane resin with surface.

Benefits of technology

It significantly improves the hydrophobicity, mechanical properties and chemical stability of polyurethane, prevents nanoparticles from agglomeration, enhances dispersion, and forms a complex network structure to improve the roughness and crosslink density of the material, significantly improves the heat resistance and mechanics of the material. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285899A_ABST
    Figure CN119285899A_ABST
Patent Text Reader

Abstract

The invention discloses polyurethane resin with a super-hydrophobic surface and a preparation method of the polyurethane resin, and belongs to the technical field of modified polyurethane materials. According to the invention, 2, 2 '-diallyl bisphenol A and a fluorine-containing thiol monomer react to introduce a fluorine-containing carbon chain, and then fluorinated modified 2, 2'-diallyl bisphenol A and tetramethoxysilane are used for treating nano zinc oxide, so that the content of active oxygen groups is reduced, a siloxane network structure is formed, the action with water molecules is reduced, and the hydrophobicity is improved. Secondly, the 2, 2 '-diallyl bisphenol A reacts with amino propyl isobutyl POSS to generate a benzoxazine structure, the POSS structure is introduced, the nano-size effect of the benzoxazine structure fills limited movement between molecular chains, a cage-shaped structure serves as a cross-linking point, the mechanical property is improved, and hydrophobicity is achieved. When polyurethane is prepared, 3, 3-bis (hydroxymethyl) azetidine and a benzoxazine structure are subjected to ring opening crosslinking, bonding, dispersity and stability of fluorinated modified nanoparticles and a matrix are enhanced, a complex network structure is formed, the surface roughness is increased, the water contact area is reduced, and super-hydrophobicity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified polyurethane materials, and in particular relates to a polyurethane resin with super-hydrophobic surface and a preparation method thereof. Background Art

[0002] Polyurethane (PU), also known as polyurethane, is a polymer material constructed by interconnecting chemical bonds such as carbamate bonds and urea bonds. It is usually prepared by reacting a compound containing two or more isocyanate groups with a compound containing two or more active hydrogens. From the perspective of the microscopic molecular segment structure, there are a large number of repeated carbamate segments on the polyurethane main chain, and hydrogen bonds can be formed between these carbamate bonds. The hydrogen bonding effect causes the PU molecular chains to be woven into a tight polymer network structure, thereby giving the polyurethane coating excellent low temperature resistance, good wear resistance, and strong chemical corrosion resistance. However, polyurethane is not hydrophobic. In certain circumstances such as being in a humid and vaporous environment for a long time, its surface is easily wetted by water. This phenomenon not only has an adverse effect on the appearance of the material, but also causes the mechanical properties, chemical stability and many other aspects of the material to decline. This is because at the molecular structure level, the polyurethane molecular chain contains a large number of polar groups such as carbamate bonds. These polar groups are extremely hydrophilic. The nitrogen atoms in the -NH- groups they contain can form hydrogen bonds with hydrogen atoms in water molecules because of their lone pair of electrons. The oxygen atoms in the -CO-O- groups can act as hydrogen bond receptors to interact with hydrogen atoms in water molecules, thereby strongly attracting water molecules to bind to them. At the same time, the flexibility of the polyurethane molecular chain is significant, and the chemical bonds in the molecular chain can rotate flexibly within a certain range. This feature enables the molecular chain to quickly adjust its own conformation when encountering water molecules, opening the door for water molecules to penetrate into the material, unlike rigid hydrophobic materials that can effectively resist the approach of water molecules.

[0003] In view of the urgent need to improve the hydrophobicity of polyurethane in practical applications, improving its hydrophobicity by modification has become a key research direction. Among them, the use of nanofillers is a common modification method. Nanofillers such as nanosilica and nanozinc oxide have unique nano-size effects, which can change the surface microstructure of polyurethane to a certain extent and increase the surface roughness. According to the superhydrophobic theory, the rough surface can capture air and reduce the actual contact area between water and the material, which is conducive to improving the hydrophobicity. However, the dispersibility of nanofillers in the polyurethane matrix is ​​a key problem that needs to be solved urgently. Nanofillers have small particle size and large specific surface area, and are prone to agglomeration. Once agglomerated, not only can they not be evenly distributed in the polyurethane matrix to play their role in enhancing hydrophobicity, but they will form stress concentration points, resulting in a decrease in the mechanical properties of polyurethane materials. Therefore, it is of great significance to develop a method that can effectively solve the problem of nanofiller dispersibility and significantly improve the hydrophobicity of polyurethane without reducing the mechanical properties of polyurethane. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention reacts 2,2'-diallyl bisphenol A with a fluorine-containing mercaptan monomer, and modifies it with tetramethoxysilane and nano zinc oxide to obtain a fluorinated modified nanoparticle solution; then reacts with polyformaldehyde and aminopropyl isobutyl POSS to obtain fluorinated modified nanoparticles grafted with POSS; finally, under nitrogen protection, diisocyanate monomers, organic tin catalysts, 3,3-di(hydroxymethyl)azetidine, diol monomers, fluorinated modified nanoparticles grafted with POSS and triethylamine are reacted to obtain a target polyurethane resin, which effectively improves the hydrophobicity, mechanical properties, heat resistance, chemical stability and other properties of the resin.

[0005] In order to achieve the above object, the following technical scheme is adopted: The present invention provides a method for preparing a polyurethane resin with a super-hydrophobic surface, comprising the following steps:

[0006] S1. Add 2,2'-diallyl bisphenol A to an acetic acid solution with a mass fraction of 1%, then add tetrahydrofuran, then add a photoinitiator to the solution, add a fluorinated thiol monomer, irradiate under ultraviolet light for 30-60 minutes, then heat to 60-85°C, add tetramethoxysilane and nano zinc oxide, and continue to react for 2-3 hours to obtain a fluorinated modified nanoparticle solution;

[0007] S2, adding paraformaldehyde and aminopropyl isobutyl POSS to 1,4-dioxane, then heating to 80-100° C., adding fluorinated modified nanoparticle solution, reacting for 8-12 hours, filtering, washing with deionized water, and drying to obtain fluorinated modified nanoparticles grafted with POSS;

[0008] S3. Under nitrogen protection, first add diisocyanate monomer and organic tin catalyst to cyclohexanone, then slowly add 3,3-di(hydroxymethyl)azetidine and diol monomer, heat to reflux, react for 3-6 hours, then cool to 40°C, add fluorinated modified nanoparticles grafted with POSS and triethylamine, maintain 40°C and continue to react for 1-2 hours to obtain the polyurethane resin with super hydrophobic surface.

[0009] Furthermore, in step S1, the mass ratio of 2,2'-diallyl bisphenol A, acetic acid solution, tetrahydrofuran, photoinitiator, fluorinated thiol monomer, tetramethoxysilane and nano zinc oxide is 1:7-12:12-15:0.15-0.4:2.5-4.5:1-3:0.5-2.

[0010] Furthermore, in step S2, the mass ratio of paraformaldehyde, aminopropyl isobutyl POSS, 1,4-dioxane and fluorinated modified nanoparticle solution is 1:0.5-1:5-10:3-6.

[0011] Furthermore, in step S3, the mass ratio of the diisocyanate monomer, cyclohexanone, diol monomer, fluorinated modified nanoparticles grafted with POSS and triethylamine is 1:3-6:0.8-1.2:0.3-0.8:0.05-0.2.

[0012] Furthermore, the fluorine-containing thiol monomer is one of 1H,1H,2H,2H-perfluorodecylthiol, 1H,1H,2H,2H-perfluorooctylthiol and 1H,1H,2H,2H-perfluorohexylthiol.

[0013] Furthermore, the photoinitiator is one of benzil ketal, benzoyl formate, benzoin dimethyl ether and 2-hydroxy-2-methyl-1-phenylpropanone.

[0014] Furthermore, the diisocyanate monomer is one or more of hexamethylene diisocyanate, 2-methylpentane-1,5-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, 2,2,4-trimethylhexane diisocyanate and 4,4′-dicyclohexylmethane diisocyanate.

[0015] Furthermore, the organic tin catalyst is one of dibutyltin dilaurate, dibutyltin diacetate, and stannous octoate.

[0016] Furthermore, the diol monomer is one of polytetrahydrofuran, polybutylene glycol, polyethylene glycol and polycaprolactone diol.

[0017] The invention also provides a polyurethane resin with a super-hydrophobic surface, which is prepared by the preparation method.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention introduces a fluorinated carbon chain through a click reaction between 2,2'-diallyl bisphenol A and a fluorinated thiol monomer, and then modifies the nano zinc oxide through fluorinated 2,2'-diallyl bisphenol A and tetramethoxysilane, thereby reducing the content of active oxygen groups on the surface of the nano zinc oxide, forming a layer of siloxane network structure on the surface of the nano zinc oxide, effectively covering the active sites on the surface of the nano zinc oxide, reducing its interaction with water molecules, thereby reducing the hydrophilicity of the material surface. The low surface energy of the fluorinated carbon chain makes the water molecules more inclined to aggregate with each other when the polyurethane resin contacts with water molecules, so that the surface of the nanoparticles has good hydrophobicity;

[0020] (2) The present invention forms a benzoxazine structure by reacting 2,2'-diallyl bisphenol A with aminopropyl isobutyl POSS, and introduces a POSS structure. The POSS structure has a unique nano-size effect and a cage structure. Its nano-size can be filled between the molecular chains of the polyurethane, restricting the movement of the molecular chains, and improving the rigidity and heat resistance of the material. The cage structure can be used as a physical cross-linking point to increase the cross-linking density of the material, further improving the mechanical properties and dimensional stability of the material. At the same time, the silicon-oxygen bond in the POSS structure has a higher bond energy, which gives the material good chemical stability and low surface energy characteristics, making the material hydrophobic.

[0021] (3) When preparing polyurethane, the present invention uses 3,3-di(hydroxymethyl)azetidine and benzoxazine structure to form a tighter chemical bond between the fluorinated modified nanoparticles and the polyurethane matrix, thereby enhancing the dispersibility and stability of the fluorinated modified nanoparticles in the polyurethane and effectively preventing the nanoparticles from agglomerating, so that they can play a better role. On the other hand, the complex network structure formed by the cross-linking reaction increases the roughness of the polyurethane surface. Since the rough surface can capture more air and reduce the actual contact area between water and the material surface, the surface hydrophobicity of the polyurethane is significantly improved, making the material surface present super-hydrophobic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The water contact angle measurement results of the polyurethane resins of various embodiments and comparative examples of the present invention;

[0023] Figure 2 The surface morphology observation SEM images of the polyurethane resins of various embodiments and comparative examples of the present invention;

[0024] Figure 3 The following are the test results of mechanical properties of polyurethane resins of various embodiments and comparative examples of the present invention.

[0025] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0028] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0029] Example 1

[0030] A polyurethane resin with super-hydrophobic surface and a preparation method thereof, the preparation method comprising the following steps:

[0031] S1. Add 2,2'-diallyl bisphenol A to a 1% acetic acid solution, then add tetrahydrofuran, then add a photoinitiator to the solution, add a fluorinated thiol monomer, irradiate under ultraviolet light for 30 minutes, then heat to 60°C, add tetramethoxysilane and nano zinc oxide, and continue to react for 2 hours to obtain a fluorinated modified nanoparticle solution;

[0032] S2, adding paraformaldehyde and aminopropyl isobutyl POSS to 1,4-dioxane, then heating to 80°C, adding fluorinated modified nanoparticle solution, reacting for 8 hours, filtering, washing with deionized water, and drying to obtain fluorinated modified nanoparticles grafted with POSS;

[0033] S3. Under nitrogen protection, first add diisocyanate monomer and organic tin catalyst to cyclohexanone, then slowly add 3,3-di(hydroxymethyl)azetidine and diol monomer, heat to reflux, react for 3 hours, then cool to 40°C, add fluorinated modified nanoparticles grafted with POSS and triethylamine, maintain 40°C and continue to react for 1 hour to obtain the polyurethane resin with super hydrophobic surface.

[0034] In the step S1, the mass ratio of 2,2'-diallyl bisphenol A, acetic acid solution, tetrahydrofuran, photoinitiator, fluorine-containing thiol monomer, tetramethoxysilane and nano zinc oxide is 1:7:12:0.15:2.5:1:0.5.

[0035] In the step S2, the mass ratio of paraformaldehyde, aminopropyl isobutyl POSS, 1,4-dioxane and fluorinated modified nanoparticle solution is 1:0.5:5:3.

[0036] In the step S3, the mass ratio of the diisocyanate monomer, cyclohexanone, diol monomer, fluorinated modified nanoparticles grafted with POSS and triethylamine is 1:3:0.8:0.3:0.05.

[0037] The fluorine-containing thiol monomer is 1H, 1H, 2H, 2H-perfluorodecyl mercaptan; the photoinitiator is benzil ketal; the diisocyanate monomer is hexamethylene diisocyanate; the organic tin catalyst is stannous octoate; and the diol monomer is polytetrahydrofuran.

[0038] Example 2

[0039] A polyurethane resin with super-hydrophobic surface and a preparation method thereof, the preparation method comprising the following steps:

[0040] S1. Add 2,2'-diallyl bisphenol A to a 1% acetic acid solution, then add tetrahydrofuran, then add a photoinitiator to the solution, add a fluorinated thiol monomer, irradiate under ultraviolet light for 60 minutes, then heat to 85°C, add tetramethoxysilane and nano zinc oxide, and continue to react for 3 hours to obtain a fluorinated modified nanoparticle solution;

[0041] S2, adding paraformaldehyde and aminopropyl isobutyl POSS to 1,4-dioxane, then heating to 100°C, adding fluorinated modified nanoparticle solution, reacting for 12 hours, filtering, washing with deionized water, and drying to obtain fluorinated modified nanoparticles grafted with POSS;

[0042] S3. Under nitrogen protection, first add diisocyanate monomer and organic tin catalyst to cyclohexanone, then slowly add 3,3-di(hydroxymethyl)azetidine and diol monomer, heat to reflux, react for 6 hours, then cool to 40°C, add fluorinated modified nanoparticles grafted with POSS and triethylamine, maintain 40°C and continue to react for 2 hours to obtain the polyurethane resin with super hydrophobic surface.

[0043] In the step S1, the mass ratio of 2,2'-diallyl bisphenol A, acetic acid solution, tetrahydrofuran, photoinitiator, fluorine-containing thiol monomer, tetramethoxysilane and nano zinc oxide is 1:12:15:0.4:4.5:3:2.

[0044] In the step S2, the mass ratio of paraformaldehyde, aminopropyl isobutyl POSS, 1,4-dioxane and fluorinated modified nanoparticle solution is 1:1:10:6.

[0045] In the step S3, the mass ratio of the diisocyanate monomer, cyclohexanone, diol monomer, fluorinated modified nanoparticles grafted with POSS and triethylamine is 1:6:1.2:0.8:0.2.

[0046] The fluorine-containing thiol monomer is 1H, 1H, 2H, 2H-perfluorooctyl thiol; the photoinitiator is benzoyl formate; the diisocyanate monomer is isophorone diisocyanate; the organic tin catalyst is dibutyltin diacetate; and the diol monomer is polybutylene glycol.

[0047] Example 3

[0048] A polyurethane resin with super-hydrophobic surface and a preparation method thereof, the preparation method comprising the following steps:

[0049] S1. Add 2,2'-diallyl bisphenol A to a 1% acetic acid solution, then add tetrahydrofuran, then add a photoinitiator to the solution, add a fluorinated thiol monomer, irradiate under ultraviolet light for 50 minutes, then heat to 75°C, add tetramethoxysilane and nano zinc oxide, and continue to react for 2.5 hours to obtain a fluorinated modified nanoparticle solution;

[0050] S2, adding paraformaldehyde and aminopropyl isobutyl POSS to 1,4-dioxane, then heating to 90°C, adding fluorinated modified nanoparticle solution, reacting for 10 hours, filtering, washing with deionized water, and drying to obtain fluorinated modified nanoparticles grafted with POSS;

[0051] S3. Under nitrogen protection, first add diisocyanate monomer and organic tin catalyst to cyclohexanone, then slowly add 3,3-di(hydroxymethyl)azetidine and diol monomer, heat to reflux, react for 4 hours, then cool to 40°C, add fluorinated modified nanoparticles grafted with POSS and triethylamine, maintain 40°C and continue to react for 1.5 hours to obtain the polyurethane resin with super hydrophobic surface.

[0052] In the step S1, the mass ratio of 2,2'-diallyl bisphenol A, acetic acid solution, tetrahydrofuran, photoinitiator, fluorine-containing thiol monomer, tetramethoxysilane and nano zinc oxide is 1:8:12.5:0.25:3:2:1.5.

[0053] In the step S2, the mass ratio of paraformaldehyde, aminopropyl isobutyl POSS, 1,4-dioxane and fluorinated modified nanoparticle solution is 1:0.8:6:7.

[0054] In the step S3, the mass ratio of the diisocyanate monomer, cyclohexanone, diol monomer, fluorinated modified nanoparticles grafted with POSS and triethylamine is 1:5:1:0.5:0.15.

[0055] The fluorine-containing thiol monomer is 1H,1H,2H,2H-perfluorohexylthiol; the photoinitiator is 2-hydroxy-2-methyl-1-phenylacetone; the diisocyanate monomer is a patent combination of isophorone diisocyanate and 1,3-di(isocyanatomethyl)cyclohexane in a ratio of 3:1; the organic tin catalyst is dibutyltin dilaurate; and the diol monomer is polycaprolactone diol.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 3 is that the nano zinc oxide is not modified, that is, an equal amount of nano zinc oxide is used to replace the fluorinated modified nanoparticles grafted with POSS, and the rest is the same as Example 3.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 3 is that the fluorinated modified nanoparticle solution is filtered and dried to replace the fluorinated modified nanoparticles grafted with POSS, and the rest is the same as Example 3.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 3 is that no 3,3-bis(hydroxymethyl)azetidine is added in step S3, that is, an equal amount of diol monomer is used to replace 3,3-bis(hydroxymethyl)azetidine, and the rest is the same as Example 3.

[0062] Results Analysis

[0063] Test Example 1

[0064] Polyurethane resin water contact angle measurement

[0065] The water contact angle of each embodiment and comparative example was measured by JC2000D7 water contact angle measuring instrument, and the results are shown in Figure 1 .

[0066] Depend on Figure 1It can be seen from the water contact angle measurement results that Examples 1-3 have higher water contact angles, and their values ​​all exceed 150°, showing super hydrophobic properties. This is because the present invention introduces fluorinated carbon chains through the click reaction of 2,2'-diallyl bisphenol A and fluorinated thiol monomers. The low surface energy characteristics of the fluorinated carbon chains make the water molecules more inclined to aggregate with each other when the polyurethane resin contacts with water molecules. At the same time, the fluorinated 2,2'-diallyl bisphenol A and tetramethoxysilane modify the nano zinc oxide, reduce the content of active oxygen groups on the surface of the nano zinc oxide, form a siloxane network structure on the surface of the nano zinc oxide, effectively cover the active sites, reduce the interaction with water molecules, and further reduce the hydrophilicity of the material surface. In addition, 3,3-di(hydroxymethyl)azetidine and benzoxazine structure are open-loop cross-linked, so that the complex network structure formed by the cross-linking reaction increases the roughness of the polyurethane surface. The rough surface can capture more air and reduce the actual contact area between water and the material surface. The synergistic effect of these factors significantly improves the surface hydrophobicity of the polyurethane, thereby greatly improving the water contact angle of Examples 1-3, which is much higher than that of the comparative example.

[0067] Test Example 2

[0068] Observation of polyurethane resin surface morphology

[0069] The surface morphology of each embodiment and comparative example was observed by JSM-6510LV scanning electron microscope, and the results are shown in Figure 2 .

[0070] Depend on Figure 2 It can be seen from the images that obvious micro-nano rough structures appear on the surfaces of the materials of Examples 1-3, which increases the roughness of the surface of the polyurethane resin. This is attributed to the complex network structure formed by the ring-opening and cross-linking reaction of 3,3-di(hydroxymethyl)azetidine and the benzoxazine structure during the preparation process. This structure presents micro-nano scale ups and downs and textures on the surface of the material. The micro-nano rough structure can effectively capture air and form a stable air layer between the material surface and the droplets. According to the Cassie-Baxter model, when the droplets contact the material surface having a micro-nano rough structure and containing an air layer, the actual contact area between the droplets and the solid surface is reduced, thereby enhancing the hydrophobicity of the material. In contrast, the surface of the comparative example is relatively flat, lacks such a micro-nano rough structure, and cannot form an effective air layer, so its hydrophobicity is poor.

[0071] Test Example 3

[0072] Polyurethane resin mechanical properties test

[0073] The tensile strength and elongation at break of each embodiment and comparative example were measured according to GBT 1040.1-2006 "Determination of tensile properties of plastics". The results are shown in Figure 3 .

[0074] Depend on Figure 3 It can be seen that Examples 1-3 exhibit better mechanical properties, and the tensile strength and elongation at break are significantly improved. This is because the present invention forms a benzoxazine structure and introduces a POSS structure through the reaction of 2,2'-diallyl bisphenol A and aminopropyl isobutyl POSS. The POSS structure has a unique nano-size effect and a cage-type structure. Its nano-size can be filled between the molecular chains of the polyurethane to restrict the movement of the molecular chains, thereby improving the rigidity of the material. The cage-type structure can be used as a physical cross-linking point to increase the cross-linking density of the material, further improving the mechanical properties and dimensional stability of the material. At the same time, when preparing the polyurethane, 3,3-di(hydroxymethyl)azetidine and the benzoxazine structure are open-loop cross-linked, so that a tighter chemical bond is formed between the fluorinated modified nanoparticles and the polyurethane matrix, thereby enhancing the dispersibility and stability of the fluorinated modified nanoparticles in the polyurethane, effectively preventing the nanoparticles from agglomerating, and enabling the nanoparticles to better bear the role of stress transfer and dispersion, thereby synergistically improving the overall mechanical properties of Examples 1-3.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0076] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polyurethane resin having a super-hydrophobic surface, characterized in that: The following steps are involved: S1. Add 2,2'-diallyl bisphenol A to an acetic acid solution with a mass fraction of 1%, then add tetrahydrofuran, then add a photoinitiator to the solution, add a fluorinated thiol monomer, irradiate under ultraviolet light for 30-60 minutes, then heat to 60-85°C, add tetramethoxysilane and nano zinc oxide, and continue to react for 2-3 hours to obtain a fluorinated modified nanoparticle solution; S2, adding paraformaldehyde and aminopropyl isobutyl POSS to 1,4-dioxane, then heating to 80-100° C., adding fluorinated modified nanoparticle solution, reacting for 8-12 hours, filtering, washing with deionized water, and drying to obtain fluorinated modified nanoparticles grafted with POSS; S3. Under nitrogen protection, first add diisocyanate monomer and organic tin catalyst to cyclohexanone, then slowly add 3,3-di(hydroxymethyl)azetidine and diol monomer, heat to reflux, react for 3-6 hours, then cool to 40°C, add fluorinated modified nanoparticles grafted with POSS and triethylamine, maintain 40°C and continue to react for 1-2 hours to obtain the polyurethane resin with super hydrophobic surface.

2. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 1, wherein: In the step S1, the mass ratio of 2,2'-diallyl bisphenol A, acetic acid solution, tetrahydrofuran, photoinitiator, fluorinated thiol monomer, tetramethoxysilane and nano zinc oxide is 1:7-12:12-15:0.15-0.4:2.5-4.5:1-3:0.5-2.

3. The method for preparing a polyurethane resin having surface super-hydrophobicity according to claim 2, wherein: In the step S2, the mass ratio of paraformaldehyde, aminopropyl isobutyl POSS, 1,4-dioxane and fluorinated modified nanoparticle solution is 1:0.5-1:5-10:3-6.

4. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 3, wherein: In the step S3, the mass ratio of the diisocyanate monomer, cyclohexanone, diol monomer, fluorinated modified nanoparticles grafted with POSS and triethylamine is 1:3-6:0.8-1.2:0.3-0.8:0.05-0.

2.

5. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 4, wherein: The fluorine-containing thiol monomer is one of 1H,1H,2H,2H-perfluorodecylthiol, 1H,1H,2H,2H-perfluorooctylthiol and 1H,1H,2H,2H-perfluorohexylthiol.

6. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 5, wherein: The photoinitiator is one of benzil ketal, benzoyl formate, benzoin dimethyl ether and 2-hydroxy-2-methyl-1-phenylacetone.

7. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 6, wherein: The diisocyanate monomer is one or more of hexamethylene diisocyanate, 2-methylpentane-1,5-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, 2,2,4-trimethylhexane diisocyanate and 4,4′-dicyclohexylmethane diisocyanate.

8. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 7, wherein: The organic tin catalyst is one of dibutyltin dilaurate, dibutyltin diacetate and stannous octoate.

9. The method for preparing a polyurethane resin having a super-hydrophobic surface according to claim 8, wherein: The diol monomer is one of polytetrahydrofuran, polybutylene glycol, polyethylene glycol and polycaprolactone diol.

10. A polyurethane resin having a super-hydrophobic surface according to any one of claims 1 to 9, characterized in that: The product is prepared by the preparation method.

Citation Information

Cited By

  • Veneering material based on crushing and recycling of genuine leather and preparation method thereof

    CN120118369A

  • Chemically modified high-strength high-temperature-resistant polyurethane fiber and preparation method thereof

    CN120889060A